Carica papaya Linn. fruit extract inhibited the activities of aldose reductase and sorbitol dehydrogenase: possible mechanism for amelioration of diabetic complications - Mutiu Idowu Kazeem; Ayotomiwa Adeyinka Adeyemi; Abiola Fatimah Adenowo; Mushafau Adewale Akinsanya (Future Journal of Pharmaceutical Sciences, 2020)
Abstract Background Diabetes mellitus is a metabolic disorder which is associated with debilitating complications including eye disease, kidney disorder, and diabetic foot disease. One of the mechanisms implicated in the pathogenesis of diabetic complications is the polyol pathway. This study evaluated the inhibitory effect of aqueous extract of four tropical fruits, namely apple (Malus domestica Borkh.), banana (Musa paradisiaca Linn.), pawpaw (Carica papaya Linn.), and watermelon (Citrullus lanatus (Thunb.) Matsum & Nakai), on the activities of polyol pathway enzymes (aldose reductase and sorbitol dehydrogenase). Results All the fruits, with the exception of banana, displayed stronger inhibition of sorbitol dehydrogenase than aldose reductase which culminated in low IC50 for the inhibition of sorbitol dehydrogenase. Of the fruit extracts tested, pawpaw inhibited both aldose reductase and sorbitol dehydrogenase most effectively with IC50 of 150.78 μg/mL and 46.30 μg/mL, respectively. Lineweaver-Burk plot also revealed that the pawpaw extract inhibited aldose reductase competitively while sorbitol dehydrogenase was inhibited in a mixed non-competitive manner. Conclusion Aqueous extract of pawpaw fruit effectively inhibited polyol pathway enzymes, and this may be attributed to rich nutritional and phytochemical composition of the fruit. Consequently, the consumption of pawpaw fruit may contribute to the amelioration of diabetic complications.